1988
DOI: 10.1007/bf00270925
|View full text |Cite
|
Sign up to set email alerts
|

Diencephalic epilepsy with congenital suprasellar arachnoid cyst in an infant

Abstract: The authors report the case of a 2-year-old infant who presented with paroxysm and short changes characterized by acute drowsiness, cold sweats, ocular reversion, facial cyanosis, and bradycardia. Between these attacks, the condition was normal, suggesting diencephalic seizures. Over 2 months five fits were observed by the parents when some to-and-fro bobbing of the head onto the trunk appeared during drowsiness. One electroencephalogram was normal without a slow background or spikes discharges. As the skull r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Salvos of yawning and irrepressible hiccupping accompany this spectacular and very unpleasant profile. The cases described reveal the presence of thalamic tumors [88,89,90,91,92]. D’Mello et al [93] also report salvos of yawns as an iatrogenic effect of vibratory massage or of the withdrawal of neuroleptics, persisting several months after convulsions are provoked.…”
Section: Excessive Yawningmentioning
confidence: 99%
“…Salvos of yawning and irrepressible hiccupping accompany this spectacular and very unpleasant profile. The cases described reveal the presence of thalamic tumors [88,89,90,91,92]. D’Mello et al [93] also report salvos of yawns as an iatrogenic effect of vibratory massage or of the withdrawal of neuroleptics, persisting several months after convulsions are provoked.…”
Section: Excessive Yawningmentioning
confidence: 99%
“…However, many authors have described the autonomic hyperactivity as consistent with the sympathetic division alone (2, 3). Lately, cases of PAH have been separated into two categories: those consisting of paroxysmal sympathetic hyperactivity in the absence of parasympathetic features and those involving a combination of sympathetic and parasympathetic hyperactivity, termed mixed autonomic hyperactivity disorders (MAHD) (4, 5). MAHD is clinically diagnosed based on the combined presence of sympathetic hyperactivity (increased heart rate (HR), respiratory rate (RR), blood pressure (BP) and body temperature (BT), sweating and papillary dilatation) and parasympathetic hyperactivity (decreased HR, RR, BP and BT, piloerection, flushing, papillary contraction, hiccups, lacrimation, yawning, and sighing) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Salvos of yawning and irrepressible hiccupping accompany this spectacular and very unpleasant profile. The cases described reveal the presence of thalamic tumors [83][84][85][86][87]. D'Mello et al [88] also reported salvos of yawns as an iatrogenic effect of vibratory massage or of the withdrawal of neuroleptics, persisting several months after convulsions are provoked.…”
Section: Excessive Yawningmentioning
confidence: 86%